The merciless II : the exorcism of Sofia Flores - Vega, Danielle (Vega, Danielle. Merciless, 2016)
Ever since Sofia's involvement with an exorcism she has been haunted by bloody visions, and when her mother dies suddenly she is sent to a creepy Catholic boarding school in Mississippi where she meets the mysterious Jude who becomes convinced that Sofia is possessed by the devil.